PENDIDIKAN MENURUT FILSAFAT PENDIDIKAN ISLAM - Chodijah, Siti (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2011)
Islam as a religion that carries the mission of mercy for the whole of nature requires a means to implement it effectively and efficiently. One of the means of its implementation is education. Thus, education should be based on the framework and vision of Islam. In line with this sense, therefore, all aspects related to education covering the goals, curriculum, teachers, methods and so forth must be reflected to the mission of Islam. Gradually, Muslims have developed educational activities ranging from the basic level up to the college level. It is proud that the resulting effort has born many encyclopedic scientists whose valuable works that can be found nowadays in a variety of science whether in terms of religious or non-religious science with its various branches. The emergence of such scientists must be ascertained due to the systematic concept and educational process. In accordance to this, nowadays we need the education concept that can produce excellent graduates who are functionally able to compete in hardly competitive society. The results of the aforementioned thought and concepts seem to be beneficial as a reflective thinking used for better future action.Â Ø§ØØªØ§Ø¬ Ø§ÙØ¥Ø³ÙØ§Ù Ø¥ÙÙ Ø§ÙÙØ³Ø§Ø¦Ù Ø§ÙØ³Ø¯ÙØ¯Ø©Â  ÙØ£Ø¯Ø§Ø¡ Ø±Ø³Ø§ÙØªÙ ÙØ±ØÙØ© ÙÙØ¹Ø§ÙÙÙÙØ ÙÙÙÙØ§ Ø§ÙØªØ±Ø¨ÙØ©.ÙÙÙØ°Ø§ ÙØ¬Ø¨ Ø£Ù ØªÙØ·ÙÙ Ø§ÙØªØ±Ø¨ÙØ© ÙÙ Ø§ÙÙØ¨Ø§Ø¯Ø¦ ÙØ§ÙØªØ¹Ø§ÙÙÙ Ø§ÙØ¥Ø³ÙØ§ÙÙØ©. Ø¥Ø°Ù ÙØ¬Ø¨ Ø£Ù ÙØ³ØªÙØ¯ Ø¥ÙÙÙØ§ Ø¬ÙÙØ¹ Ø§ÙØ¹ÙØ§ØµØ± Ø§ÙØªØ±Ø¨ÙÙØ© ÙÙ Ø§ÙØ£ÙØ¯Ø§Ù ÙØ§ÙÙØ¯Ø±Ø³ÙÙ ÙØ§ÙÙÙÙØ¬ ÙØºÙØ±ÙØ§. ÙÙØ¯ Ø·ÙÙØ± Ø§ÙÙØ³ÙÙÙÙ â ÙÙ Ø¹ÙØ¯ÙÙ Ø§ÙØ·ÙÙÙ â Ø§ÙØ£ÙØ´Ø·Ø© Ø§ÙØªØ±Ø¨ÙÙØ© Ø¨Ø¯Ø§ÙØ© ÙÙ Ø§ÙÙØ±ØÙØ© Ø§ÙØ¥Ø¹Ø¯Ø§Ø¯ÙØ© Ø¥ÙÙ Ø§ÙÙØ±ØÙØ© Ø§ÙØ¬Ø§ÙØ¹ÙØ©.ØªÙÙÙØ¯Øª ÙÙ ÙØ°Ù Ø§ÙÙØØ§ÙÙØ§Øª Ø¹ÙÙØ§Ø¡ Ø¨ÙØ§ ÙØ¯ÙÙÙ ÙÙ ÙØ¤ÙÙØ§Øª â ÙØ§ÙØ¹Ø© Ø¥ÙÙ Ø§ÙØ¢Ù â ÙÙ Ø´ØªÙ Ø§ÙÙÙÙÙ ÙØ§ÙØ¹ÙÙÙ Ø¯ÙÙÙØ© ÙØ§ÙØª Ø£Ù ÙÙÙÙØ© ØªØ¬Ø±ÙØ¨ÙØ©. Ø¸ÙÙØ± ÙØ¤ÙØ§Ø¡ Ø§ÙØ¹ÙÙØ§Ø¡ ÙÙØ³ Ø¥ÙØ§ Ø¨Ø³Ø¨Ø¨ Ø§ÙÙÙØ§ÙÙÙ ÙØ§ÙÙØ¸Ø§Ù Ø§ÙØªØ±Ø¨ÙÙ Ø§ÙÙØ·Ø¨ÙÙØ©. ÙÙØØªØ§Ø¬ Ø§ÙØ¢Ù Ø¥ÙÙ ÙÙØ§ÙÙÙ ØªØ±Ø¨ÙÙØ© ÙØªØ®Ø±ÙØ¬ ÙÙÙØ§ Ø§ÙØ®Ø±ÙÙØ¬ÙÙ Ø§ÙÙØªÙÙÙÙÙÙ Ø§ÙÙØ§ÙØ¹ÙÙ ÙÙ Ø£ÙØ³Ø§Ø· Ø§ÙÙØ¬ØªÙØ¹. ÙØ§ÙØ£ÙÙØ§Ø± ÙØ§ÙÙÙØ§ÙÙÙ Ø§ÙØªÙ ÙØ¯ÙÙÙØ§ Ø§ÙØ¹ÙÙØ§Ø¡ ÙÙ ÙØ°Ù Ø§ÙÙÙØ§ÙØ© ÙØ§Ø¨Ø¯ ÙÙ Ø§ØªØ®Ø§Ø°ÙØ§ ÙÙÙØ·Ø© Ø§ÙØ§ÙØ·ÙØ§Ù ÙÙØ§Ø¹ØªØ¨Ø§Ø± ÙØ§ÙØªÙÙÙØ± ÙÙ ØªØ·Ø¨ÙÙÙØ§ÙØ§ Ø¯Ø§ÙØª ÙØ°Ù Ø§ÙØ£ÙÙØ§Ø± ÙØ§ÙÙÙØ§ÙÙÙ ÙÙØ§Ø¦ÙØ© Ø¨Ø¹ØµØ±ÙØ§